Y6, an Epigallocatechin Gallate Derivative, Reverses ABCG2-Mediated Mitoxantrone Resistance - Zhao, Rui-Qiang; Wen, Yan; Gupta, Pranav; Lei, Zi-Ning; Cai, Chao-Yun; Liang, Gang; Yang, Dong-Hua; Chen, Zhe-Sheng; Xie, Yu-An (Frontiers in Pharmacology, 2019)
Multidrug resistance is reported to be related to the transmembrane transportation of chemotherapeutic drugs by adenosine triphosphate-binding cassette (ABC) transporters. ABC subfamily G member 2 (ABCG2) is a member of the ABC transporter superfamily proteins, which have been implicated as a key contributor to the development of multidrug resistance in cancers. A new epigallocatechin gallate derivative, Y6 was synthesized in our group. Our previous study revealed that Y6 increased the sensitivity of drug-resistant cells to doxorubicin, which was associated with down-regulation of P-glycoprotein expression. In this study, we further determine whether Y6 could reverse ABCG2-mediated multidrug resistance. Results showed that, at non-toxic concentrations, Y6 significantly sensitized drug-selected cell line NCI-H460/MX20 to substrate anticancer drugs mitoxantrone, SN-38, and topotecan, and also sensitized ABCG2-transfected cell line HEK293/ABCG2-482-R2 to mitoxantrone and SN-38. Further study demonstrated that Y6 significantly increased the accumulation of [3H]-mitoxantrone in NCI-H460/MX20 cells by inhibiting the transport activity of ABCG2, without altering the expression levels and the subcellular localization of ABCG2. Furthermore, Y6 stimulated the adenosine triphosphatase activity with a concentration-dependent pattern under 20 μM in membranes overexpressing ABCG2. In addition, Y6 exhibited a high docking score inside transmembrane domain of ABCG2. Our findings indicate that Y6 may potentially be a novel reversal agent in ABCG2-positive drug-resistant cancers.